Processos de retenção do sulfometuron-methyl em diferentes solos - Pavão, Quésia Sá (Universidade Federal Rural do Semi-Árido, 2020)
The effectiveness of the herbicide in the control of weeds depends on its availability in the soil solution to absorb the propagation structures and roots of the plants. However, this also allows the leaching of the molecule, promoting environmental contamination. Knowing the interaction between the molecule and the soil allows to predict the efficiency in the application, ensuring environmental safety. In this research, two studies were carried out to evaluate how the properties of soils can influence the behavior of sulfometuron-methyl in fifteen Brazilian soils. In the first experiment, the sorption kinetics of sulfometuron-methyl were studied to select kinetic models with the best fit to describe the sorption speed of herbicide. In the second study, the viability of the multivariate analysis technique of grouping of groups of soils with similar properties was verified, determining the sorption and desorption coefficients. Both were in a completely randomized design, performed in triplicate and the herbicide quantification was performed by high performance liquid chromatography. The sorption speed was evaluated by the batch equilibrium method and the amount absorbed and the remainder in the soil solution were used to build the kinetic models of the fifteen studied soils. The herbicide retention was estimated by the sorption constant (Kfs) and the desorption constant (Kfd) obtained by Freundlich isotherms. It was found that the pseudo-second order model is the most effective for describing the kinetics of sulfometuron-methyl. The equilibrium time of sorption was different between soils. The maximum time to reach balance was 524.4 minutes and the minimum 69.1 minutes. The multivariate analysis separated the 15 soils into 5 groups, through hydrogen potential (pH), cation exchange capacity (CEC), base saturation (BS), aluminum saturation (m). total organic carbon (TOC), and clay. It was concluded that the sorption and desorption process of the herbicide sulfometuron-methyl varies with the soil and that the efficiency of the herbicide in controlling weeds and its potential for environmental impact can be estimated based on the properties of the soil
Keywords: Cinética.; Contaminação; Interação; Planta daninha; Multivariate analysis; Kinetics; Contamination; Interaction; Weed; Análise multivariada; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA